The acute and delayed effects of foam rolling duration on male athlete's flexibility and vertical jump performance - Blades, C.: Jones, T.; Brownstein, C.; Hicks, K. (International Journal of Strength and Conditioning, 2022)
Foam rolling (FR) durations totaling =60 s per muscle are reported to acutely increase flexibility and vertical jump performance. However, limited research has investigated whether these benefits can outlast the inactive post-warmup preparatory period that typically separates warmups from the start of sporting competition. Eleven male athletes (height 1.77 0.09 m, body mass 78.0 17.0 kg, age 22 2 years) completed familiarization, followed by three experimental trials in a randomized and counterbalanced repeated measures crossover design. Trials commenced with 5 min jogging, before ankle dorsiflexion range of motion (ADF-ROM), sit and reach (S&R), countermovement jump (CMJ) and squat jump (SJ) baseline testing. Participants then sat inactively for 10 min (control) or performed lower extremity FR totaling either 30 (30FR) or 60 s (60FR) that targeted four agonist-antagonist leg muscles. Testing was then repeated before and after a simulated inactive 15 min post-warmup preparatory period to establish the acute and delayed effects of FR on performance. A two-way repeated measures analysis of variance was used to identify any significant interaction effects between conditions (30FR, 60FR, control) and timepoint (baseline, acute, delayed). No significant condition x timepoint interaction effect was detected for the ADF-ROM (f = 1.63, p = 0.19), S&R (f = 0.80, p = 0.54), CMJ ((f = 0.83, p = 0.99) or SJ (f = 0.66, p = 0.99). Therefore, FR totaling =60 s appears insufficient to enhance flexibility or vertical jump performance in male athletes.